Lugares sagrados Pataxó: entre mais-que-humanos, natureza e identidade cultural - Azevedo, Gabriela Folegatti de (Universidade Federal de São Carlos, 2021)
This work aims to list the sacred places for the Pataxó, where some of their more-than-human beings live. The aim is to establish a link between nature and spirituality and how, for the perpetuation of the Pataxó spirituality, the preservation of the forest is important. In this way, several more-than-human beings, together with the forest, take care of the Pataxó, constituting their spirituality; on the other hand, the Pataxó take care of the forest, which is the home of more-than-humans. Thus, a relationship between nature and culture is revealed, in which the Pataxó culture is linked to its places – to nature –, which makes the environmental conservation of the region fundamental. Therefore, I hope to explain how the production of the Pataxó identity has a link with the more-than-human beings that inhabit the forest and take care of the Pataxó through caring for the forest.
Pataxó sacred places: among more-than-humans, nature and cultural identity
Keywords: Índios Pataxó; Identidade; Humanos e mais-que-humanos; Cultura; Espiritualidade; Conservação ambiental; Pataxó Indians; Identity; Humans and more-than-humans; Culture; Spirituality; Environmental conservation; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA